Building A Spatial Suitability Model for Land Use in The City of Nasiriyah - Dr. Tahseen Jassim Shanan; M.M. Saja Khairuddin Mutair (Migration Letters, 2023)
This research seeks to evaluate the efficiency of urban land use in the city of Nasiriyah by using some spatial and statistical tools available in the geographic information systems environment represented by the (GIS) program. The city of Nasiriyah suffers from random and irregular spatial expansion, which was not taken into account spatial suitability. For spatial expansion and urban growth in the present and future, green lands have been encroached upon within the boundaries of the basic design of the study area, as their type has been changed from green lands to residential units as a result of weak legislation and the absence of the rule of law, especially after the events of 2003. It has become clear that there is a spatial discrepancy. The distribution of urban services at the level of the city’s neighborhoods is significant in terms of their spatial distribution and functional efficiency. It is difficult to work on redistributing those services in terms of the economic costs that will be spent on them as well as the reflection of their negative effects, whether psychological or historical, on the residents of the city of Nasiriyah. Therefore, spatial analyst applications were used within the Geographic Information Systems (GIS) environment for the purpose of building a spatial suitability model that contributes to selecting the best suitable locations for distributing urban services, including educational and health services in the city of Nasiriyah in the future, which can be based onto the basic design planners and decision makers when they choose the sites to distribute these services, a set of factors and conditions have been identified that have an impact in determining the most appropriate sites for distributing these services, classifying them, then giving them the appropriate weights, and then performing the weighted matching process (overlay), according to the weights that were given for the purpose of building a spatial suitability model in order to obtain the best locations located within the boundaries of the basic design to sign those urban uses in the city of Nasiriyah. The researcher worked to use the techniques available within geographic information systems and by relying on remote sensing data to build a model. Spatial suitability model for the most suitable locations that can be used in signing and building new urban services.